Teaching techniques and Private International Law - Carrascosa González, Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
The present work contains a reflection on the basic lines of the techniques for the teaching of Private International Law in the liquid context of the 21st century society. Professors of PrivateInternational Law must assume that this discipline is better understood with specialized teaching techniques that combine the master class with other auxiliary strategies. In this sense, private international law is perceived by students as knowledge that solves problems arising in the international society of the 21st century.